INFORMATION BEHAVIOR AND TECHNOLOGY AFFINITY AMONG HIGHER INSTITUTION LEARNERS IN BORNEO - Nurul Muizzah Johari (Proceedings of The ICECRS, 2016)
This study aims to provide an understanding of information behavior with technology based on gender. It also to investigate the relationship between information behavior and degree of technology affinity. This research has been conducted quantitatively and using survey to gain data from participants. Participant are selected randomly across Universiti Malaysia Sarawak, Sarawak. The instrument are adopted from Mills, Knezek, and Wakefield (2013) which taking interest into information behavior (ICTL) as well as technology affinity. The reliability for Information and Communication Technology Learning (ICTL) is 0.835 while for Technology Affinity Scale (TAS) is 0.831. Statistical Analysis for Social Science Package (SPSS) are used to analyze the data obtained through Independent T-test and Pearson Correlation test. Findings indicate that no significant difference found for understanding of information behavior with technology based on gender. While, another finding indicate that there is no significant relationship between information behavior and technology affinity. Improvement suggested obtain from the findings are providing understanding on the types of information behavior possess by each learner and helps educator as well as learner to plan their teaching and learning session to promote better indulgent of the knowledge.